Description and Codification of Miscanthus × giganteus Growth Stages for Phenological Assessment - Tejera, Mauricio D.; Heaton, Emily A. (Frontiers in Plant Science, 2017)
Triploid Miscanthus × giganteus is a sterile, perennial grass used for biomass production in temperate environments. While M. × giganteus has been intensively researched, a scale standardizing description of M. × giganteus morphological stages has not been developed. Here we provide such a scale by adapting the widely-used Biologische Bundesanstalt, Bundessortenamt, CHemische Industrie (BBCH) scale and its corresponding numerical code to describe stages of morphological development in M. × giganteus using observations of the “Freedom” and “Illinois” clone in Iowa, USA. Descriptive keys with images are also presented. Because M. × giganteus plants overlap in the field, the scale is first applied to individual stems and then scaled up to assess plants or communities. Of the ten principal growth stages in the BBCH system, eight were observed in M. × giganteus. Each principal stage was subdivided into secondary stages to enable a detailed description of developmental progression. While M. × giganteus does not have seed development stages, descriptions of those stages are provided to extend the scale to other Miscanthus genotypes. We present methods to use morphological development data to assess phenology by calculating the onset, duration, and abundance of each developmental stage. This scale has potential to harmonize previously described study-specific scales and standardize results across studies. Use of the precise staging presented here should more tightly constrain estimates of developmental parameters in crop models and increase the efficacy of timing-sensitive crop management practices like pest control and harvest.